Panel products from rubberwood: Particleboard, blockboard and medium density fibreboard - Mohd Nor Mohd Yusoff (Rubberwood Processing and Utilization, Kuala Lumpur, Malaysia, 1994; p185-191, 1994)
The paper deals with the potentiality of rubber wood in producing particle board, block board and medium density fiber board. It gives a detailed idea on the procedure, raw materials, properties and uses of particle board, block board and medium density fiber board and also the economic potential and the export chances of these products.
Keywords: Rubberwood products